Determinación del índice de vulnerabilidad sísmica de las viviendas existentes en tres barrios urbano marginales de la ciudad de Riobamba. - Vargas Olmedo, Ana Valeria (2013)
To find the city of Riobamba in a seismic zone where the earthquakes are unpredictable and in addition to this informal constructions in surrounding areas to the urban sector and the city of Riobamba, and inside it, which do not have the proper control and there isn’t any research assessing the resistant system that was built, the quality of materials, the environment in which structure, maintaining the same, etc. With this background was the need for this work was determined where the seismic vulnerability of 265 housing units in three urban neighborhoods marginal index such as the neighborhood José Mancero, 11 de Noviembre and San Antonio del Aeropuerto with the method Italiano and the method of the SecretaríaNacional de Gestión de Riesgos.